UPAYA PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT (Studi Kasus Pembangunan Ekonomi Kelompok Tani Desa Muara Gelumpai Kecamatan Muara Payang Kabupaten Lahat) - Pilia Angriani; Amaliatulwalidain; M. Qur’anul Kariem (TheJournalish: Social and Government, 2023)
This research aims to find out what efforts the village head has made to empower the community, especially members of farmer groups. The data collection techniques used were observation, interviews and documentation techniques using a qualitative approach. The theory used uses Munawar Noor and Edi Suharto's theory with indicators of enabling, empowering, protecting, economic, cultural and political growth. The research results show that the efforts made by the village government, in this case the village head, are still not optimal. This can be seen from the obstacles that occur, such as a). lack of socialization and guidance for farmer groups and inadequate infrastructure, b). lack of attention and strong commitment from village heads in planning programs and policies for farmer groups, c). The use of technology is still relatively simple due to the lack of application of agricultural technology and d). the lack of realization of the village fund budget which is used to empower farmer groups. From the results of this research, it can be concluded overall that the village government has not been successful in implementing community empowerment in economic development through farmer groups in Muara Gelumpai village. There are many problems ranging from unclear activities after the formation of farmer groups and the absence of programs created by the village heads themselves to empower farmer groups, resulting in new problems emerging.